2006
DOI: 10.1002/jbm.a.30737
|View full text |Cite
|
Sign up to set email alerts
|

Silicon addition to hydroxyapatite increases nanoscale electrostatic, van der Waals, and adhesive interactions

Abstract: The normal intersurface forces between nanosized probe tips functionalized with COO(-)-terminated alkanethiol self-assembling monolayers and dense, polycrystalline silicon-substituted synthetic hydroxyapatite (SiHA) and phase pure hydroxyapatite (HA) were measured via a nanomechanical technique called chemically specific high-resolution force spectroscopy. A significantly larger van der Waals interaction was observed for the SiHA compared to HA; Hamaker constants (A) were found to be A(SiHA) = 35 +/- 27 zJ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…This means that the implant is able to chemically join the bone through a strong "bioactive bond". HAP-Si was found to have increased surface adhesion compared to un-substituted HAP [6,7]. In this way, the osteointegration and the good performance of the implant are ensured [7].…”
Section: Introductionmentioning
confidence: 92%
“…This means that the implant is able to chemically join the bone through a strong "bioactive bond". HAP-Si was found to have increased surface adhesion compared to un-substituted HAP [6,7]. In this way, the osteointegration and the good performance of the implant are ensured [7].…”
Section: Introductionmentioning
confidence: 92%
“…In other studies, the bioactivity of HA-Si is explained by its surface properties and, in particular, by a negative charge localized on the rough surfaces of ceramics and sharp corners of metallic implants. [18,[25][26][27] To date, the quantity of silicon that can enter the hydroxyapatite structure has not been reliably determined. Studies have shown that it may depend on the method and conditions of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The bioactivity enhancement of Si-substituted calcium phosphates can be attributed to a number of factors that act synergistically. Si-substitution facilitates the precipitation of biological HA on implant surfaces [19][20][21] which promotes protein adsorption and osteoblast attachment and proliferation. This is added to the direct effect of Si either released to the extracellular matrix or present in the implant surface on osteoblasts, osteocalsts, and collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%